Competition of Parental Genomes in Plant Hybrids - Glombik, Marek; Bačovský, Václav; Hobza, Roman; Kopecký, David (Frontiers in Plant Science, 2020)
Interspecific hybridization represents one of the main mechanisms of plant speciation. Merging of two genomes from different subspecies, species, or even genera is frequently accompanied by whole-genome duplication (WGD). Besides its evolutionary role, interspecific hybridization has also been successfully implemented in multiple breeding programs. Interspecific hybrids combine agronomic traits of two crop species or can be used to introgress specific loci of interests, such as those for resistance against abiotic or biotic stresses. The genomes of newly established interspecific hybrids (both allopolyploids and homoploids) undergo dramatic changes, including chromosome rearrangements, amplifications of tandem repeats, activations of mobile repetitive elements and gene expression modifications. To ensure genome stability and proper transmission of chromosomes from both parental genomes into subsequent generations, allopolyploids often evolve mechanisms regulating chromosome pairing. Such regulatory systems allow only pairing of homologous chromosomes and hamper pairing of homoeologues. Despite such regulatory systems, several hybrid examples with frequent homoeologous chromosome pairing have been reported. These reports open a way for the replacement of one parental genome by the other. In this review, we provide an overview of the current knowledge of genomic changes in interspecific homoploid and allopolyploid hybrids, with strictly homologous pairing and with relaxed pairing of homoeologues.